Characterization of family IV UDG from Aeropyrum pernix and its application in hot-start PCR by family B DNA polymerase. - Xi-Peng Liu (Public Library of Science (PLoS), 2011)
Recombinant uracil-DNA glycosylase (UDG) from Aeropyrum pernix (A. pernix) was expressed in E. coli. The biochemical characteristics of A. pernix UDG (ApeUDG) were studied using oligonucleotides carrying a deoxyuracil (dU) base. The optimal temperature range and pH value for dU removal by ApeUDG were 55-65°C and pH 9.0, respectively. The removal of dU was inhibited by the divalent ions of Zn, Cu, Co, Ni, and Mn, as well as a high concentration of NaCl. The opposite base in the complementary strand affected the dU removal by ApeUDG as follows: U/C≈U/G>U/T≈U/AP≈U/->U/U≈U/I>U/A. The phosphorothioate around dU strongly inhibited dU removal by ApeUDG. Based on the above biochemical characteristics and the conservation of amino acid residues, ApeUDG was determined to belong to the IV UDG family. ApeUDG increased the yield of PCR by Pfu DNA polymerase via the removal of dU in amplified DNA. Using the dU-carrying oligonucleotide as an inhibitor and ApeUDG as an activator of Pfu DNA polymerase, the yield of undesired DNA fragments, such as primer-dimer, was significantly decreased, and the yield of the PCR target fragment was increased. This strategy, which aims to amplify the target gene with high specificity and yield, can be applied to all family B DNA polymerases.